Highly diastereoselective oxy-Michael additions of enantiopure delta-lactol anions to nitroalkenes: asymmetric synthesis of 1,2-amino alcohols. - Adderley, N; Buchanan, D; Dixon, D; Lainé, D (2003)
The "naked" alkoxide 1 of (S)-6-methyl-δ-lactol acts as an excellent chiral hydroxide equivalent in highly diastereoselective oxy-Michael additions to nitroalkenes (see scheme). The excellent stereoinduction arises from what becomes a superb protecting group in the resulting 1,2-amino alcohol products. R1 = alkyl, aryl, furanyl, thiophenyl; R2,R 3 = -(CH2)3CHCH3O-.